Development of transmission usage allocation scheme for deregulated power systems - Mustafa, Mohd. Wazir; Mohd. Khalid, Saifulnizam (Faculty of Electrical Engineering, 2008)
Developing a fair and an equitable real and reactive power allocation method has been an active topic of power research particularly in the new paradigm, with many transactions taking place at any time. However, due to non linear nature of power flow, it is difficult to determine transmission usage allocations accurately. Therefore, it required using circuit theories, approximate models, tracing algorithms or sensitivity indices for usage allocation. This project suggests Modified Nodal Equations methodology to allocate the real and reactive power output of individual generators to system loads. The purpose is to represent each load current as a function of the generators’ current and load voltages. Starting from the concept of circuit theory, it uses the modified admittance matrix to decompose the load voltage dependent term into components of generator dependent terms. By applying Kirchhoff’s laws and using the decompose components of load current and load voltages, the real and reactive power contribution from each generator to loads in a deregulated power system operating as a power pool are determined. Moreover, the line usage allocation for pool and bilateral trades is developed on the basis of tracing and circuit method respectively. It further enhanced the methodology by utilizing an appropriate Artificial Neural Network (ANN) to solve the generator’s contribution to loads and line usage allocation in a simpler and faster manner. In this project, a feedforward and Radial Basis Function Network (RBFN) architecture have been chosen to incorporate into Modified Nodal Equations method for the proposed ANN transmission usage allocation technique. Both the feedforward and RBFN output provide the results in a faster and convenient manner with very good accuracy. Adaptation of appropriate ANN architectures for a large test system is expected to deliver a considerable efficiency in computation time especially during training processes. Finally, a new and an improved transmission usage allocation method have been developed for future of the Malaysian electric energy sector.